2022
DOI: 10.3389/fnagi.2022.806054
|View full text |Cite
|
Sign up to set email alerts
|

Altered Brain Activity in Depression of Parkinson’s Disease: A Meta-Analysis and Validation Study

Abstract: BackgroundThe pathophysiology of depression in Parkinson’s disease (PD) is not fully understood. Studies based upon functional MRI (fMRI) showed the alterations in the blood-oxygen-level-dependent (BOLD) fluctuations in multiple brain regions pertaining to depression in PD. However, large variance was observed across previous studies. Therefore, we conducted a meta-analysis to quantitatively evaluate the results in previous publications and completed an independent regions-of-interests (ROIs)-based analysis us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 54 publications
(64 reference statements)
0
3
0
Order By: Relevance
“…Altered functional connectivity of ventral striatal subregions and between ventromedial putamen and left middle occipital gyrus provided new insight into neural mechanisms of depression in early PD (Wang et al 2022 ). Recent functional MRI studies characterizing the spontaneous blood–oxygen-level-dependence (BOLD) in the whole brain and multiple brain regions revealed reduction in the resting-state BOLD complexity as an important component in the pathology of DPD (Liu et al 2022 ), and a meta-analysis and validation study demonstrated altered BOLD activity in posterior cingulate gyrus, supplementary motor area and cerebellum in DPD compared to non-depressed ones (Su et al 2022 ).…”
Section: Dpd and Brain Circuit Disturbancesmentioning
confidence: 99%
“…Altered functional connectivity of ventral striatal subregions and between ventromedial putamen and left middle occipital gyrus provided new insight into neural mechanisms of depression in early PD (Wang et al 2022 ). Recent functional MRI studies characterizing the spontaneous blood–oxygen-level-dependence (BOLD) in the whole brain and multiple brain regions revealed reduction in the resting-state BOLD complexity as an important component in the pathology of DPD (Liu et al 2022 ), and a meta-analysis and validation study demonstrated altered BOLD activity in posterior cingulate gyrus, supplementary motor area and cerebellum in DPD compared to non-depressed ones (Su et al 2022 ).…”
Section: Dpd and Brain Circuit Disturbancesmentioning
confidence: 99%
“…This capability has advanced the development of physiological-physical models, which serve as a means to investigate and rehabilitate the brain state in patients, providing a framework for understanding the mechanisms underlying neural restoration. Moreover, several fMRI studies have shown that Parkinson's disease patients exhibit altered blood-oxygen-level dependent (BOLD) functional connectivity (FC) between different anatomical regions of a large-scale brain network [34][35][36][37] . Previous research has shown that mean FCs in areas such as the primary motor cortex, premotor cortex, and supplementary motor areas are attenuated in Parkinson's disease patients as compared to healthy controls (HCs) 38 .…”
Section: Introductionmentioning
confidence: 99%
“…Secondly, the etiology of depression is complicated and includes social, genetic and psychological factors (13,14). Previous studies reported that the manifestation and severity of depression are not only affected by factors such as gender, educational level, marital status, and income but also depend on other comorbid conditions including stroke, thyroid problems and Parkinson's disease (PD) (15)(16)(17)(18)(19)(20). Importantly, a single nucleotide variation in the oxoglutarate dehydrogenaselike gene rs2293239 (p.Asn725Ser) was identified as a major genetic predictor of familial depression (21).…”
Section: Introductionmentioning
confidence: 99%